Unlocking English Proficiency: The Impact of Mobile Assisted Language Learning on First-Semester Students at Pamulang University” - Darmawati; Neneng Misliyah (CV. Shofanah Media Berkah, 2024)
In the quest to enhance English proficiency among first-semester students at Pamulang University, this research delves into the effectiveness of mobile-assisted language learning (MALL). With the burgeoning integration of mobile technology into educational paradigms, particularly in the realm of language acquisition, there exists a burgeoning curiosity surrounding its potential impact on students' linguistic development. In this study, MALL is introduced as a supplementary tool alongside traditional classroom instruction, aiming to elucidate its influence on the English language competencies of first-semester students. Employing a qualitative methods approach, this research intertwines assessments of language proficiency levels with in-depth qualitative analyses of students' perceptions and experiences with MALL. Qualitative data is meticulously collected through an array of methodologies including, interviews, and reflective journals, allowing for a nuanced exploration of students' attitudes towards MALL and its perceived impact on their language learning journey. Findings from this research illuminate the multifaceted impact of MALL on first-semester students' English proficiency. Through qualitative analysis, it becomes apparent that students perceive MALL as a valuable tool for augmenting their language learning experience. The integration of mobile technology fosters increased engagement, personalized learning opportunities, and heightened motivation among students. Moreover, MALL serves as a catalyst for autonomous learning, empowering students to take ownership of their language acquisition journey. Despite some challenges such as technological barriers and time management constraints, the overall consensus among students indicates a positive correlation between MAL usage and enhanced English proficiency. This research not only contributes to the growing body of literature on mobile assisted language learning but also provides valuable insights for educators and institutions seeking to optimize language learning experiences in tertiary education settings. By embracing the potential of MALL and its capacity to unlock English proficiency, Pamulang University and similar institutions can embark on a trajectory towards fostering linguistic excellence and global competence among their student populace.